Pola Komunikasi Organisasi Dalam Pelaksanaan Event Lomba Tingkat Nasional - Jisca Putri Sagara Hati; Detya Wiryany; Ridma Meltareza (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
CREATIN photography competition event: Creative Moment INABA Photography Contest is a national level competition held to provide a platform for students from various universities to create high quality images based on a specific theme. The main purpose of this event is to encourage creativity, appreciate the art of photography, and promote the potential of young photographers, especially among students. This research uses a qualitative case study method to understand the phenomenon in depth. The focus of the research is a national-level photography competition event held by INABA University with the theme "The Quiet Street". Purposive sampling was used to select informants, and data collection techniques included direct observation of the planning, organizing, implementing, and controlling of the event. The results showed that the use of the POAC framework in organizing the national photography competition event provided clear guidance in planning, organizing, implementing, and monitoring and evaluating the event. Careful planning, good organization, coordinated execution, and continuous monitoring and evaluation helped overcome obstacles and ensure the success of the event. The final evaluation provides important insights for the committee to improve the quality of future events.